Optical transparency and silica network structure in cross-linked natural rubber as revealed by spectroscopic and three-dimensional transmission electron microscopy techniques - Atsushi Kato (2018)
Through the study of particulate-silica-filled cross-linked natural rubber, an optical characteristic phenomenon involving a transition from transparency to opacity and reentry to transparency with an increase of silica loading is reported and examined using ultraviolet/visible spectroscopy and haze and diffusion transmittance measurements. Additionally, three-dimensional transmission electron microscopy observation and volume resistivity measurements reveal that the silica is in a networklike structure in the rubbery matrix. Combining these experimental results with a few theoretical considerations, the characteristic phenomenon is estimated to originate from the optical multiple scattering due to isolated chains of silica, which are present in the networklike structure of silica, but one end of which is not connected to the networks even after the percolated silica network is formed. © 2008 Optical Society of America.